2019
DOI: 10.1002/jrsm.1344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating network meta‐analysis and inconsistency using arm‐parameterized model in structural equation modeling

Abstract: Network meta-analysis (NMA) uses both direct and indirect evidence to compare the efficacy and harm between several treatments. Structural equation modeling (SEM) is a statistical method that investigates relations among observed and latent variables. Previous studies have shown that the contrastbased Lu-Ades model for NMA can be implemented in the SEM framework. However, the Lu-Ades model uses the difference between treatments as the unit of analysis, thereby introducing correlations between observations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Current direct-indirect evidence inconsistency models have also been shown to fall under a class of model which splits the inconsistency parameter between the treatments of interest. 7,12,13 However, the split weights in these models are assigned either out of convenience or symmetricity, rather than solid theoretical justifications. We have shown that our evidence-splitting model implies that the split weights should be proportional to the marginal variance of each treatment outcome, which is guided by the intuition of evidence independence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Current direct-indirect evidence inconsistency models have also been shown to fall under a class of model which splits the inconsistency parameter between the treatments of interest. 7,12,13 However, the split weights in these models are assigned either out of convenience or symmetricity, rather than solid theoretical justifications. We have shown that our evidence-splitting model implies that the split weights should be proportional to the marginal variance of each treatment outcome, which is guided by the intuition of evidence independence.…”
Section: Discussionmentioning
confidence: 99%
“…Current direct‐indirect evidence inconsistency models have also been shown to fall under a class of model which splits the inconsistency parameter between the treatments of interest 7,12,13 . However, the split weights in these models are assigned either out of convenience or symmetricity, rather than solid theoretical justifications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations